Exemplars of Curriculum Theory. - Ellis, Arthur K. (Taylor and Francis, 2013)
This book crosses the divide between theoreticians and practitioners by demonstrating how curriculum theories and models are applied in classrooms today. It ties together broad educational theories such as progressivism, essentialism, perennialism, etc; curriculum models, characterized as learner-centered, society-centered or knowledge-centered; and exemplars of curriculum theories and models, such as Reggio Emilia, Core Knowledge, the International Baccalaureate, etc.